(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
An ancient ghost is going around the Western World promotinga ‘novel’ thesis that claims to be based ona ‘fresh’ look of the subject in question. Although the ‘novelty’ of this ‘thesis’ is meant to appearinnovative and based on ‘new’ research, it can be easily traced back to its origins. The alleged ‘new’ thesis was invented byareinvigorated revisionism of the First World War unfolding an agenda of pushing the responsibility for its unleashing away from Germany and Austria-Hungary to France, Russia, Great Britain, and Serbia. A few historians in England and Germany – with a different focus – are trying to leave the vast international historiography on the origins of the war behind and turn the conclusions, that once were a ‘consensus’ internationally, upside down.